Factor Analysis of Interest in Buying Products on TikTok, Product Reviews, Live Streaming Selling and Discounts - Diyah Mulyani; Budi Sukardi (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
With the emergence of TikTok as a leading platform for commercial activities, understanding the dynamics of consumer behavior in this context has become a necessity for businesses. By examining the interactions between these variables, this research aims to provide insight into the effectiveness of product reviews, live streaming selling, and discounts in shaping consumer interest in TikTok. The population in this study are residents in Solo Raya who own or are TikTok users, and the sample in this study was 300 respondents. This research uses multiple linear regression analysis to determine the factors that influence interest in purchasing products on TikTok, with a focus on product reviews, live streaming sales and discounts. The research results show that all independent variables have a positive and significant effect on buying interest